Increasing the Competence of Physics Teachers in Designing PjBL-Based Teaching Aids for the Implementation of the Merdeka Curriculum - Mairizwan Mairizwan; Hidayati Hidayati; Wahyuni Satria Dewi; Renol Afrizon; Roni Jarlis (Postgraduate, University of Mataram, 2022)
AÂ visual aidÂ is an object that can be used as a support for physical science activities. Teaching aids can be designed by the teacher using readily available materials. The competence of physics teachers in Pasaman Barat Regency has not been optimal in compiling PjBL-based Physics teaching aids student worksheets. So, the facts found in the field show that the professional competence and pedagogical competence of physics teachers in Pasaman Barat Regency in physics learning are not optimal. Therefore, it is necessary to increase the competency of Physics teachers in designing PjBL-based teaching aids. This type of research is quasi-experimental research. The treatment is in the form of assistance in making teaching aids based on PjBL. Bimtek activities in the form of practical assistance increase the competency of activity participants, which in this case are Physics teachers in Pasaman Barat Regency. The increase in the competence of physics teachers in Pasaman Barat Regency in making PjBL-based physics teaching aids was 24.17%. In addition, the mentoring activities provided are effective for increasing the mastery of MGMP Physics teachers in the Pasaman Barat Regency of the PjBL model material. This activity is also helpful for teachers designing teaching aids to support Physics learning as an merdeka curriculum implementation